PERILAKU KONSUMEN UNTUK MENGAKSES SUARAMERDEKA.COM - Demartha Hayu Waseso; Ismi Darmastuti (Faculty of Economics and Business Diponegoro University, 2013)
This Research was triggered by the development of the internet and appearance of sites. The advantages of news sites are provide information quickly and accessible than newspaper. Suaramerdeka.com is one of news sites, because intense competition, so the site is less enthused. Suara Medeka promoted the sites by using social media and their newspaper. This research aimed to determine the effect of promotion, website quality, and company reputation on accessing decision on suaramerdeka.com. In this research, the data was collected using such as questionnaires given to 75 respondents, in order to determine respondent’s responses to each variable. The analysis used in this research includes Validity Test, Reliability Test, Classic Assumption Test (normality test, multicollinearity test, heteroscedasticity test), Multiple Linear Regression Analysis and Goodness Of Fit (f-test), t-test and Coefficient Of Determination. From the results ofregressionanalysiscan be known that Promotion, Website Quality, and Company Reputation have positive effect on Accessing Decision at suaramerdeka.com which competitive Website Quality is the most influential variable on purchasing decisions, followed by Promotion and Company Reputation. 51.8 % of accessing decision could be explained by promotion, website quality, and company reputation, while the remaining 48.2% could be explained by other variables. Keywords : Promotion, Website Quality, Company Reputation, Accessing Decision.